The kinetics of oxidation of aluminum electroexplosive nanopowders during heating in air; Russian Journal of Physical Chemistry A; Vol. 84, № 9 - Korshunova A. V.; Ilyin A. P. Aleksandr Petrovich; Radishevskayab N. I.; Morozovaa T. P. (2010, 2010)
The rules governing the oxidation of aluminum nanopowders obtained by the electrical explosion of wires during heating in air under the conditions of linearly increasing temperature and in isothermal regime were studied. The influence of the composition and structure of aluminum particle oxide coating and metallic core on the parameters of the process and the phase composition and morphology of oxidation products was determined. Thermal reaction conditions were shown to depend on thermogravimetry regime, and the kinetic data were used to explain this dependence. The kinetics of oxidation was modeled taking into account the aluminum particle-size distribution function. It was shown that the structures of particles of the nanodisperse and micron electroexplosive powder fractions were different.